2020
DOI: 10.1055/s-0040-1713605
|View full text |Cite
|
Sign up to set email alerts
|

Quality Improvement to Reduce Neonatal CLABSI: The Journey to Zero

Abstract: Neonatal infections, including those associated with central lines, continue to be a major cause of morbidity and mortality despite many other improvements in neonatal outcomes. Over the past decades, significant advances have been made to reduce central line-associated bloodstream infections (CLABSIs) using quality improvement methodology. This article will review pertinent studies that used both the Institute for Healthcare Improvement Model for Improvement and other innovative techniques such as orchestrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
7
0
2
Order By: Relevance
“…A systematic review and network meta-analysis of the adult population demonstrated that antimicrobial-impregnated CVCs significantly reduced the CLABSI rate compared with standard catheters (15). The early insertion, use of glue, MST insertion technique, single lumen catheters, a small number of attempts, and the use of lipid emulsion to facilitate the guidewire removal are all significantly higher in the miconazole and rifampicinimpregnated catheter and are all supposed to reduce the CLABSI rate (25,35,36). On the other hand, the birth weight and the gestational age were significantly lower in the miconazole and rifampicin-impregnated catheter group together with the longer dwell time compared with the conventional PICC.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and network meta-analysis of the adult population demonstrated that antimicrobial-impregnated CVCs significantly reduced the CLABSI rate compared with standard catheters (15). The early insertion, use of glue, MST insertion technique, single lumen catheters, a small number of attempts, and the use of lipid emulsion to facilitate the guidewire removal are all significantly higher in the miconazole and rifampicinimpregnated catheter and are all supposed to reduce the CLABSI rate (25,35,36). On the other hand, the birth weight and the gestational age were significantly lower in the miconazole and rifampicin-impregnated catheter group together with the longer dwell time compared with the conventional PICC.…”
Section: Discussionmentioning
confidence: 99%
“…2022;21:e59515 mãos e preparação da pele (14,17) . É fato que a higienização das mãos é a medida mais simples e de menor custo para a prevenção das infecções relacionadas a assistência à saúde, visto a complexidade da assistência à saúde do neonato, sendo imprescindível o incentivo, adesão a essa medida e a implementação dos bundles como primordial (18,19) .…”
Section: Silva Agrs Alves Sb Neves Hcc Mendonça Km Santos Slv Moreira...unclassified
“…Entretanto, deve ser ter cautela na utilização de clorexidina, principalmente a solução alcoólica, devido ao risco de lesão de pele, especialmente, em prematuros extremos (21) . A existência de uma variedade de estratégias tanto na inserção e como na manutenção do CVC evidencia a necessidade de conhecimento e avaliação antecipada do local ou unidade de implantação, para elaborar estratégia personalizada de acordo com as características e necessidade da instituição (19,21) . A segurança do paciente em UTIN neonatal, que inclui a prevenção e controle de IRAS, requer várias medidas primordiais, dentre elas, a necessidade de mudanças culturais em relação à segurança do paciente e à formação dos profissionais, à inserção da família no cuidado e à assistência humanizada (22) .…”
Section: Silva Agrs Alves Sb Neves Hcc Mendonça Km Santos Slv Moreira...unclassified
“…Given the associated morbidity and financial burden of CLABSI, quality improvement processes and research endeavors must persist to minimize CLABSI across the nation. Through measures such as a vascular access team, multidisciplinary involvement, and bundles, we can continue to reduce the incidence and impact of neonatal CLABSIs with the ultimate goal of getting to zero [14].…”
Section: Central Line-associated Bloodstream Infectionsmentioning
confidence: 99%